Efficiency and determinants of entry into Malaysian palm oil refinery industry - Choo, Sze Yi (2016)
The palm oil refinery industry became the key industry following the nation’s economic transition plan in the early 1970s, where it is since known as the workhorse of palm oil industry. The refinery industry began to boom with the establishment of refineries in several states in the early days spreading in Peninsular Malaysia and to Sabah and Sarawak in recent years. The issues of efficiency and competitiveness of refinery industry are brought to question as to what causes the downtrend of capacity utilisation rate, why a refinery country has been importing refined palm oil and export crude palm oil (CPO) instead of producing processed palm oil (PPO) locally and the slow entry of new refineries. This study aims to examine the entry and efficiency of the Malaysian palm oil refinery industry from the period of 2005 to 2013. The non-parametric Data Envelopment Analysis (DEA) approach of Malmquist Total Factor Productivity (TFP) indices are employed to examine efficiency of the industry, while the discrete choice logit model is adopted to identify factors related to entry in the industry. The DEA approach includes panel data analysis of 34 Malaysian palm oil refinery firms. The empirical results indicate that only 14.7% of the firms in the industry are closed to the frontiers or on the frontier across all efficiency indices. On average, palm oil refinery industry has not been performing well with regress in four out of five efficiency indices. Technical efficiency change exhibits a drop of -0.3%, technological change declines - 1.3%, pure efficiency change is down by -0.3%, and total factor productivity change declines -1.6% respectively. Scale efficiency change is the only indicator that shows slight progress of 0.1% over the estimation period of 2007 to 2013. The empirical analyses of logit model are conducted using panel data of 52 Malaysian palm oil refinery firms. The empirical findings of logit model on all 52 firms indicate that profit rate (positive), minimum efficient scale (negative) and distribution and marketing intensity (negative) variables exhibit expected coefficient signs and are significant. The logit analysis on 35 public listed firms is significant where profit rate (positive), growth (positive), minimum efficient scale (negative) and distribution and marketing intensity (negative) carried the expected coefficient signs. The statistically significant p-values of these analyses directly indicate that the overall influence of independent variables is considered significant on entry in this model. Consumption and demand for palm oil will continue to rise in the future given its wide application in our daily lives. As palm oil industry is the key industry to the economic growth of Malaysia, it should be studied extensively to ensure its growth and development is in line with the world’s need for the product. The empirical findings suggest that vertical integration is necessary to allow domestic refineries to enjoy complete supply chain in their production. Refineries would therefore be able to enjoy continuous inputs and cheaper raw materials for refining processing. It is also essential for refineries to boost productivity, efficiency and competitiveness in both domestic and global markets through adoption of advanced technologies in machineries, equipments and refinery plants. Refineries ought to amplify their production scale to attain economies of scale in production to enjoy lower cost advantage and higher utilisation rate. In addition, large scale entry through mergers and acquisition of small firms are necessary to expand the operation of small firms and to encourage healthy competition among refineries. Collaboration between government’s agencies and refineries are essential in encouraging development in the said industry.